Exchange Rate Determination: A Model of the Decisive Role of Central Bank Cooperation and Conflict - Robin Pope; Reinhard Selten; Sebastian Kube; Johannes Kaiser; Jürgen von Hagen (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
Opinion is divided on whether it is better to have a single world money or variable exchange rates. Pope, Selten and von Hagen (2003) propose that fresh light would be shed via an analysis that allows for seven complexity impacts on the exchange rate that are underplayed (where not entirely absent) from current analyses: 1) the role of official sector, including its central bank; 2) the numerous official and private sector goals; 3) the disparate degrees of market power of different sorts of private agents; 4) the documentation that essentially all shocks to the exchange rate are generated by human decisions; 5) the non-maximising heuristics that in the complex economy agents use; 6) heterogenous beliefs. This paper analyses a closed form game theoretic solution of version 1 of a model that combines impacts 1 to 4 with the conventional finance assumption that all agents maximise their utility. Impact 1) precludes private agents being able to destabilise the exchange rate against the cooperation of the central banks required by the game theoretic solution. Impact 4) excludes random events and other exogenous shocks such as meteors falling from the sky. The rational maximising assumption in turn precludes all other sources of shocks and thus any need for a variable exchange rate to equilibrate after shocks. We then modify version 1 of our model substituting for the maximising assumption impacts 5 to 7, impacts that allow shocks from humans to be consistently incorporated. We do so by means of an experimental investigation which indicates that central bankers less than fully cooperate, leaving scope for private speculators to support their preferred currency. From the viewpoint of the game theoretic equilibrium, the resultant exchange rate changes render equilibrium unspecified. A single world money avoids disruptive exchange rate changes from less than fully cooperating central banks, exchange rate changes caused by central bank conflicts and that cannot be classified as equilibrating.
Keywords: F31; F33; B40; B59; C79; C90; C91; C92; 330; central bank; cooperation; conflict; exchange rate; experiment; market power; heuristics; heterogenous beliefs; personality; interpersonal dynamics; friendship; complex; destabilising speculators; irrational central bankers